A Theoretical and Analytical Review of Global Health Diplomacy: Creating Global Enviromental Health towards Sustainable Development’s Goals - Nugraheni, Nadea Lathifah (UNIDA Gontor, 2023)
Health diplomacy becomes an even more critical element in significant issues that needed to negotiate for health in the face of other interest. The role of diplomacy in health is vital. Good health and well- being require a clean and harmonious in many aspects. Health depends on where people live. Nowadays emergencies,conflict and disasters happen frequently, including natural disasters,chemichal or radiological incidents,complex emergencies and deliberate events. A substantial fraction of the disease burden derived from these events is attributable to enviromental risks factors which is link to health emergencies. WHO as the director and coordinator authority on international health within United Nations systems has responsibility to protect public health and supporting lead enviroment and to build a better and healthier future for people. This paper argues that The Sustainable Development Goals are not only target for WHO but for all agencies in different aspects. In regard of creating enviromental health, as the only global agency with the mandate to cover the while health agenda, WHO should continue to work closely with other patners in the UN family and beyond, and target- specific work is should be strenghtened as well.